2014
DOI: 10.1002/csr.1352
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility on Customer Satisfaction, Relationship Maintenance and Loyalty in the Shipping Industry

Abstract: This paper aims to examine the impact of perceived corporate social responsibility (CSR), with a focus on ethical and environment questions related to the constructs of customer satisfaction (CS), relationship maintenance (RM) and customer loyalty (CL), on determining the attitudinal and behavioural loyalty and maintenance of customers in the shipping industry. For this purpose, this study enhances its empirical validity by collecting data from 214 respondents in South Korea and testing the hypothesis using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 85 publications
(140 reference statements)
6
114
0
2
Order By: Relevance
“…It means that if top tourism agencies of Tehran tend to grasp customer's satisfaction favorably in order to achieve the competitive advantage, should deeply consider customers' expectations and also how to implement it with a social approach emphasizing on CSR. The results of this hypothesis converge research of Shin and Thai (2015).…”
Section: Review Of European Studiessupporting
confidence: 82%
“…It means that if top tourism agencies of Tehran tend to grasp customer's satisfaction favorably in order to achieve the competitive advantage, should deeply consider customers' expectations and also how to implement it with a social approach emphasizing on CSR. The results of this hypothesis converge research of Shin and Thai (2015).…”
Section: Review Of European Studiessupporting
confidence: 82%
“…The marketing literature has provided strong evidence supporting that customer satisfaction has a positive effect on customer loyalty (Shin & Thai, 2015). It has been acknowledged that repeated satisfaction is a key condition, or at least for the initial formation of loyalty (Oliver, 2010).…”
Section: The Mediating Role Of Customer Loyaltymentioning
confidence: 99%
“…A growing literature stream has found that consumers take into consideration a company's CSR practices in their evaluation of a firm and in their purchase decisions (Luo & Bhattacharya, 2006;Maignan, 2001;Öberseder et al, 2014;Perera & Chaminda, 2013). In this line, most studies have addressed the influence of CSR consumer on identification with the company, satisfaction, and loyalty (He & Li, 2011;Pérez & Rodríguez del Bosque, 2015;Shin & Thai, 2015). Nevertheless, Öberseder et al (2013, p. 1840) point out that 'these contributions offer a narrow interpretation, operationalization (e.g.…”
Section: Introductionmentioning
confidence: 99%